Delayed cord clamping and inotrope use in preterm infants. (19th May 2018) - Vesoulis, Zachary A.; Rhoades, Janine; Muniyandi, Pournika; Conner, Shayna; Cahill, Alison G.; Mathur, Amit M.
Abstract: Objective: To evaluate the impact of delayed cord clamping (DCC) on need for inotropic support and mean arterial blood pressure (MABP). Methods: This is a single-center, prospective case-control study of premature infants, born <32 weeks gestation, who underwent DCC in comparison to a matched control group who underwent immediate cord clamping (ICC). The primary outcomes were the differences in MABP and inotropic medication used over the first week of life. Secondary outcomes included the admission hemoglobin, need for blood transfusion, and rates of intraventricular hemorrhage (IVH). Infants were matched on EGA, birth weight, sex, antenatal corticosteroid and magnesium exposure, and presence of chorioamnionitis. Results: Hundred and fifty-eight infants (DCC n  = 79, ICC n  = 79) were included. Demographic factors were similar between groups. DCC infants had a higher admission hemoglobin ( p  < .01), reduced incidence of high-grade IVH ( p  = .03), fewer median transfusions ( p  = .03), and were discharged at an earlier post-menstrual age ( p  = .04). When controlling for other factors, DCC was not associated with a reduction in inotrope use ( p  = .22) but was associated with a reduction in high-grade IVH ( p  = .01). There was no difference in MABP between the groups. Conclusions: DCC is not associated with a reduction in the use of inotropes or a difference in MABP.